2022
DOI: 10.1371/journal.pone.0266440
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of seasonal influenza and influenza vaccine immunization among people visiting primary healthcare centers in Riyadh, Saudi Arabia

Abstract: Influenza infection continues to be a hazard to the Saudi population, resulting in high death rates and illness prevalence; it also places a substantial financial burden on the government. The government takes several strategies and approaches through the Ministry of Health has shown great success in curbing the disease. Vaccination is considered the most appropriate control measure; unfortunately, most Saudi residents, particularly in the city of Riyadh, do not consider vaccination a safe health practice. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 26 publications
5
11
2
Order By: Relevance
“…On the other hand, the rate of vaccination coverage in the current study seems low. This deserved more analysis of the causes underlying reluctance to get the vaccine, as our findings and those of previous studies indicate that previous vaccination increases the likelihood of getting the vaccine again, presumably as those individuals possess good knowledge about the vaccine's safety and hold a positive attitude (12,14,23,24) .…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…On the other hand, the rate of vaccination coverage in the current study seems low. This deserved more analysis of the causes underlying reluctance to get the vaccine, as our findings and those of previous studies indicate that previous vaccination increases the likelihood of getting the vaccine again, presumably as those individuals possess good knowledge about the vaccine's safety and hold a positive attitude (12,14,23,24) .…”
Section: Discussionsupporting
confidence: 52%
“…Another key finding of the current study is the relatively low (45%) flu vaccination rate among the participants, and a large group of non-vaccinated participants gave no specific reason (73%). The rates of flu vaccination among the general population in KSA generally ranged from 42.9% to 55% (12)(13)(14)(15) . The rates among healthcare workers in KSA ranged from 41% to 67% (16)(17)(18)(19)(20) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, over 80% of Saudi Arabian caregivers refused to get their child vaccinated against influenza. Furthermore, a study conducted in various primary healthcare facilities in the capital city of Saudi Arabia demonstrated that, many people lack awareness of the influenza virus and its vaccine, hold strong misconceptions about side effects and believe it is useless [6,7]. A cross-sectional survey in Saudi Arabia reported that 82% of the respondents, who were adults, prefer to take precautions against the COVID-19 infection rather than take the vaccine [8].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike in the western countries, the factors that predict caregivers' readiness to vaccinate children in the age group [5][6][7][8][9][10][11]…”
Section: Introductionmentioning
confidence: 99%